High-frequency B-dot probes used to detect characteristics of ion cyclotron range of frequency waves in EAST. (April 2019) - Liu, Lunan; Zhang, Xinjun; Qin, Chengming; Zhao, Yanping; Yuan, Shuai; Mao, Yuzhou; Wang, Jianhua
Abstract : The plasma in the scrape-off layer (SOL) has an important effect on the coupling of the waves in the ion cyclotron range of frequencies (ICRF). The high-frequency B-dot (HFB) probes have been installed to investigate the behaviour of ICRF waves on EAST. The fast and slow ICRF wave field amplitudes are measured and a domain parallel wavenumber is deduced. Results of measurements on a test experimental platform and EAST experiments are presented, which include vacuum and plasma situations. In vacuum it is found that field amplitudes increase linearly with ICRF power. Besides, during plasma operation, field amplitudes measured were decreased by an order of magnitude and no linear relation with power was observed. Fast and slow wave power densities fluctuate strongly with plasma density. The experimental results in the laboratory coincide with the simulation results and allow for validating of the measurement method.